Eficacia del tratamiento fisioterapéutico en pacientes con radiculopatías que acuden al centro medical rehabilitic en el periodo julio- diciembre 2010 - Flor Cadena, Myriam Adriana (2010)
With ageing originates intervertebral disc and longitudinal ligament, mediated by dehydration that causes loss of the height of the disc degeneration. The above joined the repeated microtraumas. These can be both axial compressions or, more commonly, traumatized while bending. Forced bending generates previous disk compression which presses the nucleus pulpous backwards. If the posterior region of fibrous ring is weakened or torn, bending allows the extrusion pulpous ring from the defect of continuity. The disc cans get a hernia on address side, central or centrolateral. Most frequent location: Cervical C5-C6 and C6-C7, and Lumbar L4-L5 L5-S1. 70 % of adults suffer (low back pain) lumbar pain at some point in his life, but only 1-2 % of these are caused by a herniated disc. Back pain is a symptom, not a diagnosis and affects 70-80 % of the population.